Analysis of a Markovian Retrial Queue With Working Vacation Under N-Control Pattern - Manoharan, P.; Bala Murugan, S. Pazhani (Communications in Mathematics and Applications, 2022)
A Markovian retrial queue with working vacation under N-control pattern is investigated in this article. To describe the system, we employ a QBD analogy. The model’s stability condition is deduced. The stationary probability distribution is generated by utilizing the matrix-analytic technique. The conditional stochastic decomposition of the line length in the orbit is calculated. The performance measures and special cases are designed. The model’s firmness is demonstrated numerically.
Keywords: Markovian retrial queue; Working vacation; N-control pattern; Conditional stochastic decomposition